Feedback controls in physiology and medicine - Raman, A. (University Of Malaya, 1980)
The cells, tissues and organs of living organisms are not random collections of physical and chemical elements, but intricately organized arrangements of systems of interacting parts and processes. The per-formance of a living organism is not that of its Clements. but that of its systems such as the nervous, cardiovascular, respiratory, endocrine and so n. The study of living organisms begins with an analysis, in isolation, f the component parts that make up though systems, but it must proceed o synthesis in which the emergent behavior of the whole animal is examined. Since living things are mostly self-regulating and selfmaintaining, it is obvious that there must be controls of the various systems to regulate and counteract any changes that may occur within the animal. The study of physiology is therefore nothing more than a study of the various systems in the body and the feedback controls that are involved in the regulation of these systems.